Anti-Bullying Characters Based on Hadith: Controlling Your Mouth and Hands: Karakter Anti Bullying Berbasis Hadis: Mengendalikan Lisan Dan Tangan - Saifullah, Saifullah; Hadi , Muhammad Fazlurrahman; Cahyadi , Rahmat Arofah Hari (Universitas Muhammadiyah Sidoarjo, 2025)
The phenomenon of bullying in the educational environment continues to be a serious concern because of its detrimental impact on students' mental, social and spiritual development. From an Islamic perspective, bullying behavior is contrary to teachings that emphasize love, respect and protection of others. One of the important guidelines in building an anti-bullying character is the hadith of the Prophet Muhammad, which reads: